Adipose cells induce phospho-Thr-172 AMPK production by epinephrine or CL316243 in mouse 3T3-L1 adipocytes or MAPK activation and G protein-associated PI3K responses induced by CL316243 or aluminum fluoride in rat white adipocytes - Ohsaka, Y; Nishino, H; Nomura, Y (Folia biologica, 2014)
Responses of adipose cells to adrenoceptor regulation, including that of β-adrenoceptor (AR), and the signalling machinery involved in these responses are not sufficiently understood; information that is helpful for elucidating the adrenoceptor (adrenergic and β-AR)-responsive machinery is insufficient. We examined phospho-Thr-172 AMPK production in mouse-derived 3T3-L1 adipocytes treated with epinephrine or CL316243 (a β3-AR agonist) for 15 min. We also examined MAPK activation or G protein-associated PI3K activation or -associated PI3K p85 complex formation in rat epididymal (white) adipocytes treated with CL316243 for 15 min or aluminum fluoride (a G-protein signalling activator) for 20 min. Furthermore, we examined the effect of PTX (a trimeric G-protein inactivator) on p85 complex formation induced by aluminum fluoride treatment. Western blot analysis revealed that epinephrine or CL316243 treatment increased the phospho- Thr-172 AMPK (an active form of AMPK) level in 3T3-L1 adipocytes. Activated kinase analysis with a specific substrate showed that CL316243 or aluminum fluoride treatment activated MAPK in rat adipocytes. Immunoprecipitation experiments with a G-protein β subunit (Gβ) antibody showed that treatment of rat adipocytes with CL316243 activated PI3K and increased the PI3K p85 level in the Gβ antibody immunoprecipitates. Such an increase in the p85 level was similarly elicited by aluminum fluoride treatment in a PTX-sensitive manner. Our results provide possible clues for clarifying the signalling machinery involved in adrenoceptor responses, including those of β3-AR, in mouse-derived adipocytes and rat white adipocytes. Our findings advance the understanding of responses to adrenoceptor regulation in adipose cells and of the cellular signalling machinery present in the cells.
Keywords: fosfatidylinositol-3-kinasy; AMP-Activated Protein Kinases; pertusový toxin; fosfothreonin; Pertussis Toxin; buňky 3T3-L1; Aluminum Compounds; proteiny vázající GTP; 3T3-L1 Cells; Phosphatidylinositol 3-Kinases; Immunoprecipitation; GTP-Binding Proteins; fluoridy; adrenalin; krysa rodu Rattus; Epinephrine; Animals; bílé tukové buňky; Adipocytes, White; Mitogen-Activated Protein Kinases; Fluorides; Dioxoles; zvířata; Rats; imunoprecipitace; dioxoly; myši; Mice; proteinkinasy aktivované AMP; mitogenem aktivované proteinkinasy; sloučeniny hliníku; Phosphothreonine